Optimal deployment and traffic flows in mobile mesh network after a disaster. (2017) - Wang, Junbo; Cheng, Zixue
It is a critical research problem to quickly reconstruct a communication system after a disaster. One resolution is to deploy mobile mesh routers (MMR) in the disaster area to guarantee the connection of users. However, it is still a challenge to find an optimal deployment of MMRs to maximally satisfy users while ensuring a fluent and reliable communication network. In this paper, we focus on the above problems and propose a communication-demand-oriented deployment method (CDODM) and a global-data-traffic routing optimisation method (GTFROM) for a disaster. Our main contributions are (1) formalisation and optimisation of computation transmission cost in CDODM and (2) formalisation and optimisation traffic flows in GTFROM. Through the evaluation in NS3, user satisfaction calculated based on recorded throughput in NS3 can be enhanced clearly in the proposed solutions. In scalability study, the proposed methods works well, with changing range of disaster areas, number of MMRs and communication demands.